Bile Acid Supplementation Improves Murine Pancreatitis in Association With the Gut Microbiota - Wan, You-Dong; Zhu, Rui-Xue; Pan, Xin-Ting; Sun, Tong-Wen (Frontiers in Physiology, 2020)
Disorders of bile acids (BAs) are closely related to the development of liver and intestinal diseases, including acute pancreatitis (AP). However, the mechanism underlying the involvement of BAs in AP development remains unclear. We used intraperitoneal injection of cerulein to construct AP mouse models. These mice had significantly reduced tauroursodeoxycholic acid (TUDCA) and an imbalance of intestinal microbiota, based on 16S rDNA gene sequencing. To explore the role of AP-induced intestinal microbiota changes in the development of AP, we transplanted the stool obtained from AP mice to antibiotic-treated, microbiota-depleted healthy mice. Microbiota-depleted mice presented injury to the intestinal barrier function and pancreas. Additionally, microbiota depletion reduced AP-associated pancreatic injury. This indicated that the gut microbiota may worsen AP. As TUDCA was deficient in AP mice, we gavaged AP mice with it, and evaluated subsequent expression changes in the bile acid signaling receptors farnesoid-x-receptor (FXR) and its target gene fibroblast growth factor (FGF) 15. These were downregulated, and pancreatic and intestinal barrier function injury were mitigated. The gut microbiota is known to regulate bile acid production and signaling, and our analysis of changes to the gut microbiota in AP indicated that Lactobacilli may be the key contributors of TUDCA. Taken together, our study shows that supplementation with BAs could reduce pancreatic and intestinal injury, and that this effect may be associated with the gut microbiota.